Hemodynamics New Diagnostic and Therapeutic Approaches - Seda Artis, A. (IntechOpen, 2012)
Hemodynamics is study of the mechanical and physiologic properties controlling blood pressure and flow through the body. The factors influencing hemodynamics are complex and extensive. In addition to systemic hemodynamic alterations, microvascular alterations are frequently observed in critically ill patients. The book "Hemodynamics: New Diagnostic and Therapeuric Approaches" is formed to present the up-to-date research under the scope of hemodynamics by scientists from different backgrounds.